(untitled) (Academia Science Repository, 2023)
The dysfunction of kidney functions is one of the most common diseases among people on a global scale. This disease can be classified as low levels of renal infiltration rate less than 60 ml/min. and the renal failure disease were divided into five stages that are evaluated through some important parameters, which include glomerular filtration rate, urea and creatinine levels in serum.